PERENCANAAN PELAKSANAAN PROYEK PEMBANGUNAN SUDARMA CONDOTEL DI JALAN MAHENDRADATTA DENPASAR - Gusti Ayu Sukma Dwi Naindia Sari; I Putu Gede Suranata (Program Studi Teknik Sipil, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2018)
Implementation Planning on the Project of Sudarma Condotel aim to start plan and complete project targets within existing limitations to meet project spesifications within limits cost, quality and time. To maximize implementation planning then an analysis is carried out method, manufacture of Standard Operational Procedure (SOP), estimated project duration, resource requirements planning, resource scheduling and cost planning so that an achievement schedule can be used project guidelines. The result of Sudarma Condotel planning with total duration is 347 working days with cost implementation plan of cost budget plan including 10% PPN for Rp. 8.290.900.557.